Major obstetric hemorrhage: a follow-up survey on quality of life of women and their partners - Giel van Stralen; Laurine L. M. Ruijten; Ad A. Kaptein; Ron Wolterbeek; Jos van Roosmalen (Taylor & Francis Group, 2018)
Introduction: A description is given of the quality of life (QOL) of women who were treated with peripartum embolization or hysterectomy for major obstetric hemorrhage (MOH). Methods: Questionnaires assessing QOL, combined with questionnaires and drawings assessing illness perceptions, were used to compare women with MOH to reference groups provided by the questionnaires. Results: Women who experienced MOH have similar scores on QOL questionnaires compared to reference groups. Women treated with arterial embolization scored better than women treated with hysterectomy. Partners of women with MOH scored better on QOL questionnaires than reference groups. Drawings reflect the major emotional impact of MOH. Discussion: MOH does not seem to have a negative effect on QOL 6-8 years after the event, although drawings and verbalizations indicate major emotional impact. More extensive follow-up is advised for early recognition of the need for psychological help. Women after embolization seem to have better QOL compared to women after hysterectomy.